Correlation Between Unilateral Free End Edentulous and Morphological Variations of Condyle Using Panoramic Radiographs - Ramadan Ariesta Putra; Shinta Amini Prativi; Valentino Haksajiwo (Sriwijaya Journal of Dentistry, 2021)
Background: Unilateral free end edentulous can cause a habit of one side chewing which will affect the condition of the temporomandibular joint (TMJ) mechanism. The TMJ is a complex joint consisting of the glenoid fossa, mandibular condyle and disc articular. No previous studies have examined the correlation between free end edentulous and morphological variations in the mandibular condyles. Purpose: to determine the correlation between unilateral free end edentulous and morphological variations of condyle using panoramic radiographs at South Sumatera RSKGM. Methods: This analytic observational study was using 68 samples of panoramic radiographs at RSKGM South Sumatra in September 2019 - March 2020. The sample was divided into 34 unilateral free end edentulous and 34 complete teeth. The condyle morphology of each sample was traced, and the data obtained were analyzed using the Chi-square method in the SPSS application. Results: Morphological abnormalities of the condyles were more frequently seen in patients with unilateral free end edentulous conditions, that is 41.18%. While in patients with complete teeth, the visible abnormalities of the condyles was only 5.88%. There was a significant correlation between unilateral free end edentulous and morphological variations of mandibular condyles (p<0.005). Conclusion: There is a correlation between unilateral free end edentulous and morphological variations of condyle using panoramic radiographs in Dental Hospital of South Sumatera Province.